Karakteristik Pengetahuan Orang Melayu (Studi Epistemologi pada Cerita Rakyat Sumatera) - Syefriyeni Syefriyeni (Intizar, 2018)
This paper is motivated by a kind of academic questions, or anxieties towards; like what traditional people used to answer the phenomena that exist in the middle of their lives. The answers will certainly be a reference, even as a knowledge, perhaps not yet in the scientific category, but knowledge only. Knowledge that is created or raised is in order to answer the questions of human on natural, social and sociocultural phenomena, and so on. The author sees that one side of the presence of this knowledge is in folklore. That said, because traditional society usually answers the questions of their children and grandchildren about natural phenomena and others, presented in words such as a series of stories. Or, explain about threats and punishments and behavioral replies. Regardless of the scientific or not, as long as the words and stories are able to answer people's thirst, or explain anything at that time about certain questions, then that is the knowledge that is present in their time. For this reason, the author wants to see what knowledge is presented in the folklore, how it is characterized. This research uses philosophical, qualitative, and hermeneutical methods. The result of this research is that folklore is able to provide knowledge about ethical values. Establish knowledge, and answer certain regional histories, and natural phenomena for the provision of daily life.